Revisiting the spider genus Eutichurus Simon, 1897 (Araneae, Eutichuridae): new species and complementary descriptions - Bonaldo, Alexandre B.; Lise, Arno A.; Ramírez, Martín J.; Saturnino, Regiane (Zootaxa, 2018)
Six new species of the genus Eutichurus Simon, 1897 are described: E. murgai new species (based on male and female) and E. paredesi new species (male) from Peru; E. cumbia new species (female) and E. tequendama new species (male) from Colombia; E. yungas new species (male and female) from Bolivia, and E. nancyae new species (male and female) from Brazil. The males of E. marquesae Bonaldo, 1994, E. madre Bonaldo, 1994 and E. zarate Bonaldo, 1994 are described for the first time. Eutichurus brescoviti Bonaldo, 1994, described on males, is synonymized with E. tropicus (L. Koch, 1866), previously known only from females. New records for E. ibiuna Bonaldo, 1994, E. ravidus Simon, 1897, E. putus O. Pickard-Cambridge, 1898, E. silvae Bonaldo, 1994, E. lizeri Mello-Leitão, 1938, E. saylapampa Bonaldo, 1994, E. tropicus and E. manu Bonaldo, 1994 are presented. A key to all species of Eutichurus is provided, variation in the epigynal morphology of E. ibiuna is recorded and the fine morphology of E. marquesae is documented.